Projected Effect of Droughts on Supply, Demand, and Prices of Crops in India - Kumar, P.; Joshi, P.K.; Aggarwal, Pramod K. (2014)
This paper assesses the effect of monsoon droughts on the production, demand, and prices of seven major agricultural commodities - rice, sorghum, pearl millet, maize, pigeon pea, groundnut and cotton. A partial generalised equilibrium model is developed to simulate the effects of deficit rainfall on acreage, yield, production, demand, and prices of different agricultural commodities in India. It is used to project the effect of rain deficits on supply, demand, and prices of monsoon session crops.